IDENTIFICATION OF LACTIC ACID BACTERIA (BAL) FROM BIOFLOC from TECHNOLOGY WITH TAPIOCA CARBON SOURCES IN RED TILAPIA IN CULTIVATION MEDIA (Oreochromis sp.) - Suci Wulandari; Henni Syawal; Iesje Lukistyowati; Iskandar Putra (Berkala Perikanan Terubuk, 2019)
This study aims to determine the types of lactic acid bacteria grown at different pH from floc (clots) which are given carbon sources of tapioca and can increase the number of bacteria in the medium of red tilapia cultivation. The method used is the survey method and experiment by growing bacteria on different pH treatments, namely pH 2, 4 and 6, growing colonies were identified based on morphological and biochemical characteristics. The results of identification found 13 isolates of lactic acid bacteria (BAL) which only grew at pH 4 and 6 of these isolates consisted of the genus Bacillus and Streptococcus. The total bacteria in the cultivation medium ranged from 2x108 to 7x108 CFU / mL.